Is Complete Excision Always Enough? A Quality of Sexual Life Assessment in Patients with Deep Endometriosis - Raluca Gabriela Enciu; Octavian Enciu; Dragoș Eugen Georgescu; Adrian Tulin; Adrian Miron (Medicina)
Background and Objectives: The aim of this study was to find the factors associated with the severe impairment of QoSL and the factors associated with a better score in QoSL, as well as the evaluation of pain symptoms and QoSL after the complete and incomplete excision of rectovaginal nodules. Materials and methods: The present prospective study was conducted in a single tertiary center for endometriosis where 116 patients underwent laparoscopic surgery for deep endometriosis during a 3-year period. The goal of the intervention was to excise all endometriotic implants while conserving the rectum. Intraoperative findings were recorded after the intervention, and the patients were classified according to the ENZIAN classification and rASRM scores. QoSL was assessed using the EHP-30 Module C (QoSL Score). Results: When comparing the mean scores before and 2 years after the surgery, a highly significant improvement was found for QoSL and dysmenorrhea (p < 0.0001). The complete excision of rectovaginal nodules led to a significantly better QoSL and lower dyspareunia (p < 0.0001) than incomplete resection (p < 0.02). Conclusions: This prospective study proves that the complete laparoscopic excision of all endometriotic implants improved the QoSL and decreased the pain score of dyspareunia. Incomplete rectovaginal nodule excision was correlated with a poorer QoSL and a lower improvement of dysmenorrhea, dyspareunia, and chronic pelvic pain scores than complete excision.